2011
DOI: 10.1590/s0103-84782011000300028
|View full text |Cite
|
Sign up to set email alerts
|

Elaboração de biscoitos de chocolate com substituição parcial da farinha de trigo por polvilho azedo e farinha de albedo de laranja

Abstract: Os consumidores estão cada vez mais exigentes e preocupados com a saúde e, por consequência, exigindo produtos naturais que deverão ser seguros e promover qualidade de vida. O presente trabalho teve o objetivo de desenvolver biscoitos com farinhas mistas de polvilho azedo e farinha de albedo de laranja, utilizando um planejamento fatorial 2³, com variáveis independentes: concentração de polvilho azedo, açúcar e farinha de albedo de laranja, e variáveis respostas: as características sensoriais: aparência, aroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
29

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 4 publications
0
3
0
29
Order By: Relevance
“…The significant differences observed among the developed formulations, might have occurred by different percentages of the supplemental ingredients in each formulation (Table 1), leading to changes in weight and providing greater water retention, due to the fiber content of the sweet biscuits. Santos et al (2011a), also reported higher values compared to standard, when researching cookies prepared with buriti flour, with and without addition of oatmeal in the formulation.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…The significant differences observed among the developed formulations, might have occurred by different percentages of the supplemental ingredients in each formulation (Table 1), leading to changes in weight and providing greater water retention, due to the fiber content of the sweet biscuits. Santos et al (2011a), also reported higher values compared to standard, when researching cookies prepared with buriti flour, with and without addition of oatmeal in the formulation.…”
Section: Resultsmentioning
confidence: 87%
“…A number of studies using industrial residues from food processing have been performed with this purpose (Lacerda et al, 2009;Santos et al, 2011a;Yoshiara et al, 2012). A viable alternative, not yet exploited by the food industry, is the use of agro-industrial coproducts in the technological development of sweet biscuits, once they have nutritional support and ease of incorporation into food formulations, culminating in a final product with significant food appeal, and contributing to their total use, avoiding the irregular disposal and minimizing environmental pollution (Henningsson et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Para o resíduo mineral ixo, teores mais elevados foram encontrados nas formulações contendo 35% de amêndoa de baru, tanto para o chocolate meio amargo quanto para o chocolate amargo. Santos et al (2011), ao avaliarem biscoito de chocolate acrescido de polvilho, obtiveram valores de umidade de 2,10 ± 0,12 g.100…”
Section: Composição Centesimalunclassified
“…Diversos estudos vêm sendo realizados com a substituição de parte da farinha de trigo por outras fontes de fibras ou proteínas, visando incrementar o valor nutricional de biscoitos, como, por exemplo, a adição de fécula de mandioca, polvilho azedo e albedo de laranja (SANTOS et al, 2010(SANTOS et al, , 2011, farinha de aveia e farinha de arroz parboilizado (ASSIS et al, 2009) Avaliação física e sensorial de biscoitos tipo cookie adicionados de farelo de trigo e arroz FEDDERN, V. et al www.ital.sp.gov.br/bj milimetrada, antes e uma hora após o forneamento. Nesse momento, a espessura (cm) foi verificada com paquímetro.…”
Section: Introductionunclassified